2022
DOI: 10.1177/1525822x221077398
|View full text |Cite
|
Sign up to set email alerts
|

Short Take: Collecting Data from a Vulnerable Population during the COVID-19 Pandemic

Abstract: Conducting field research with a vulnerable population is difficult under the most auspicious conditions, and these difficulties only increase during a pandemic. Here, we describe the practical challenges and ethical considerations surrounding a recent data collection effort with a high-risk population during the COVID-19 pandemic. We detail our strategies related to research design, site selection, and ethical review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Findings show that recruitment through peer networks using RDS was possible across all subgroups during COVID-19. Numerous studies have shown the efficacy of RDS ( 28 , 29 ) in recruiting PWID and HIV+ marginalized populations, but the onset of COVID-19 seems to have disrupted social networks that underpin this methodology, slowing recruitment ( 30 ). While those in the HIV+ PWID subgroup managed to recruit from other subgroups of HIV- PWID and HIV+ and not PWID, this occurred at a lower frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Findings show that recruitment through peer networks using RDS was possible across all subgroups during COVID-19. Numerous studies have shown the efficacy of RDS ( 28 , 29 ) in recruiting PWID and HIV+ marginalized populations, but the onset of COVID-19 seems to have disrupted social networks that underpin this methodology, slowing recruitment ( 30 ). While those in the HIV+ PWID subgroup managed to recruit from other subgroups of HIV- PWID and HIV+ and not PWID, this occurred at a lower frequency.…”
Section: Discussionmentioning
confidence: 99%